GPS antenna design with slotted ground plane - Sim, Chow-Yen-Desmond; Han, Tuan-Yung (Microwave and optical technology letters, 2008)
A single layer, single‐feed circularly polarized (CP) microstrip antenna designed with 2 pairs of slot embedded on its ground plane for global positioning system (GPS) is proposed. The experimental results shown that by simply tuning the length of the slotted pair, two orthogonal near‐degenerate resonant modes for CP radiation can be excited. By comparing the proposed antenna to a reference antenna of similar sizes with two pairs of slit embedded on the radiating square patch; the proposed antenna demonstrated enhancement in gain, bandwidth, and radiation efficiency. Furthermore, in comparison to other CP antennas with slotted ground plane design, it demonstrated an excellent F/B ratio and wide 3 dB beamwidth. © 2008 Wiley Periodicals, Inc. Microwave Opt Technol Lett 50: 818–821, 2008; Published online in Wiley InterScience (www.interscience.wiley.com). DOI 10.1002/mop.23215